2019
DOI: 10.3390/s19102219
|View full text |Cite
|
Sign up to set email alerts
|

Fast 2D Laser-Induced Fluorescence Spectroscopy Mapping of Rare Earth Elements in Rock Samples

Abstract: Due to the rapidly increasing use of energy-efficient technologies, the need for complex materials containing rare earth elements (REEs) is steadily growing. The high demand for REEs requires the exploration of new mineral deposits of these valuable elements, as recovery by recycling is still very low. Easy-to-deploy sensor technologies featuring high sensitivity to REEs are required to overcome limitations by traditional techniques, such as X-ray fluorescence. We demonstrate the ability of laser-induced fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The two emission bands represent 4 F 3/2 -4 I 11/2 and 4 F 3/2 -4 I 9/2 transitions, respectively (e.g. Reisfeld et al, 1996;Gaft et al, 2005;Czaja et al, 2012;Shalapska et al, 2014). Emission bands at shorter wavelengths (< 850 nm; Gaft et al, 2005) were not observed during measurements and hence are not recorded in our phosphate reference spectra.…”
Section: Ree Reference Spectra At 325 Nm Laser Excitationmentioning
confidence: 95%
See 3 more Smart Citations
“…The two emission bands represent 4 F 3/2 -4 I 11/2 and 4 F 3/2 -4 I 9/2 transitions, respectively (e.g. Reisfeld et al, 1996;Gaft et al, 2005;Czaja et al, 2012;Shalapska et al, 2014). Emission bands at shorter wavelengths (< 850 nm; Gaft et al, 2005) were not observed during measurements and hence are not recorded in our phosphate reference spectra.…”
Section: Ree Reference Spectra At 325 Nm Laser Excitationmentioning
confidence: 95%
“…In general, it overlaps with the characteristic Ce 3+ emission band around 360 nm that is associated with a 5d-4f transition (e.g. Reisfeld et al, 1996;Gaft et al, 2005;Shalapska et al, 2014). Several studies report broadened Ce-related peaks and discuss reasons behind them; for example, Shalapska et al (2014) identified a peak doublet with the peak distance dependent on the site symmetry in the crystal lattice, and Chen et al (2014) observed broadened emission in the range between 310 and 410 nm resulting from mixed phases of a monoclinic and hexagonal lattice.…”
Section: Ree Reference Spectra At 325 Nm Laser Excitationmentioning
confidence: 98%
See 2 more Smart Citations
“…Fluorescence spectroscopy is a technique wherein incoming photons excite optical centers within a material, which then emit a specific spectrum as the centers return to the ground state. [17][18] In solids, optical centers can be ion inclusions in the host, or defects in the solid matrix. Optical centers are not ionized, unlike for XRF, and so electrons in excited states are still bound to the host mineral.…”
Section: Introductionmentioning
confidence: 99%